2020
DOI: 10.1101/2020.01.30.926576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conventional dose rate spatially-fractionated radiation therapy (SFRT) treatment response and its association with dosimetric parameters – A preclinical study in a Fisher 344 rat model

Abstract: 2728 Abstract 29 Purpose: To identify key dosimetric parameters that have close associations with tumor treatment 30 response and body weight change in SFRT treatments with a large range of spatial-fractionation 31 scale at dose rates of several Gy/min. 32 Methods: Six study arms using uniform tumor radiation, half-tumor radiation, 2mm beam array 33 radiation, 0.3mm minibeam radiation, and an untreated arm were used. All treatments were 34 delivered on a 320kV x-ray irradiator. Forty-two female Fischer 344 rat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The resulting optimum ctc distances and mean cell survival levels are reported in Table 1. The minimum dose of the heterogeneous irradiation is set equal to the mean dose of conventional irradiation approaches since it mainly qualifies the tumor control 24 . This leads indispensably to an increase of the mean dose of heterogeneous irradiations by a factor f D compared to the homogeneous irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting optimum ctc distances and mean cell survival levels are reported in Table 1. The minimum dose of the heterogeneous irradiation is set equal to the mean dose of conventional irradiation approaches since it mainly qualifies the tumor control 24 . This leads indispensably to an increase of the mean dose of heterogeneous irradiations by a factor f D compared to the homogeneous irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid cold spots within the heterogeneously irradiated tumor volume, the mean dose may be elevated such that a minimum required dose for tumor control is obtained even in the dose valleys. It has already been proven by Rivera et al that the valley dose is the most relevant parameter for tumor control 24 .…”
Section: The Enhanced Mean Clonogenic Cell Survival Through Large Ctcmentioning
confidence: 97%
“…27 Compared with MRT, MBRT employs a larger scale planar beam width of several hundred microns. 36 Consequently, MBRT beams may be generated using any one of the widely available small animal X-ray irradiators, which makes its study more relevant to potential clinical translation and application as compared with MRT, which is typically generated only at a handful of synchrotron facilities around the world. 37 Remarkably, in animal studies, the ultrahigh M(B) RT dose (several hundred Gy peak dose) is well tolerated by normal tissue while producing tumor control and survival comparable to conventional BRT.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously characterized some of the unique dosimetric parameters of different forms of SFRT (including MBRT, the form of SFRT used in this work) and their correlations with treatment responses in a recent preclinical study. 36 In animal studies, high-dose MRT and MBRT have shown an extremely high tissue-type selectivity, eradicating tumors without damaging or inhibiting the function of normal tissues that are exposed to the same high-dose radiation. 25,27 The extraordinary M(B)RT effect may stem from its unique spatial and dosimetric characteristics, which are radically different than those of conventional broadbeam radiation therapy (BRT).…”
Section: Introductionmentioning
confidence: 99%